(untitled) (International Conference on Computers in Education, 2022)
In the learning science community, technology-based interventions afford educators and learners opportunities to augment their classrooms through engaging, interactive simulations that ground concepts in embodied experiences. The current study developed and deployed a visual novel platform called The Hidden Village-Online (THV-O) that used emulated 3D-motion-capture to offer students opportunities to use their bodies as a means for thinking geometrically. This paper discusses the design process for developing THV-O (e.g., narrative, UX, scaffolds) and data from a small within-subjects randomized design experiment using THV-O. Researchers administered a geometry unit using THV-O in which players performed game-directed actions prior to evaluating geometry conjectures. Students’ game performance data, audio (transcripts), and video (gestures) data were processed and analyzed. Results indicated that students whose spoken responses included representational (depictive) and dynamic (enactive) gestures showed greater accuracy for intuitions, insights, and formations of transformational proofs.